Seismic performance improvement of conventional timber brace using re-centring friction connection. (August 2020) - Mohamad Mahdi Yousef-beik, Seyed; Bagheri, Hamed; Veismoradi, Sajad; Zarnani, Pouyan; Hashemi, Ashkan; Quenneville, Pierre
Highlights: Seismic response of the conventional timber braces has been improved by a re-centring friction connection. A framework has been developed to design the conventional timber braces to have a ductile failure mode. Abstract: The Conventional Timber Brace (CTB) is a simple and economical lateral load resisting system capable of providing a suitable elastic (initial) stiffness, thanks to the stiff behavior of the timber in parallel to the grain direction. However, their inelastic behaviour, appearing in case of major seismic events, is a matter of concern mainly because of the degradation of both ultimate strength and elastic stiffness. This issue is normally cited as the pinching effect in the literature and originates from the arrival of timber crushing in the end connections. The main focus of this paper is; accordingly, placed on introducing a new timber brace with alleviated end connection performance. More specifically, the aim is achieved by replacing the conventional connection with a new damage-free self-centring connection, named Resilient Slip Friction Joint (RSFJ) to form a new self-centring timber brace (SC-TB). To evaluate the efficiency of the proposed system, an experimental testing program was considered where a number of scaled specimens were experimentally tested. At the final stage of this study, a comparative study is presented in which the seismic performance of a 4 storey archetype building using SC-TB is compared with that of a building with CTB. According to the results, the performance of the building with the proposed SC-TB outperformed the CTB one in terms of the base shear, not having a pinched response and possessing a reusable damping resource.